2011
DOI: 10.2298/jsc101218141a
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the essential oils of Citrus sinensis cv. valencia and a quantitative structure-retention relationship study for the prediction of retention indices by multiple linear regression

Abstract: The chemical composition of the volatile fraction obtained by head-space solid phase microextraction (HS-SPME), single drop microextraction (SDME) and the essential oil obtained by cold-press from the peels of C. sinensis cv. valencia were analyzed employing gas chromatography-flame ionization detector (GC-FID) and gas chromatography-mass spectrometry (GC-MS). The main components were limonene (61.34 %, 68.27 %, 90.50 %), myrcene (17.55 %, 12.35 %, 2.50 %), sabinene (6.50 %, 7.62 %, 0.5 %) and α-pinene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 20 publications
2
12
1
1
Order By: Relevance
“…Other study showed that the C. sinensis peel EO had limonene, β-myrcene, decanal, β-pinene, and linalool, as major compounds with good antioxidant activity [70]. Limonene in the present study reached 73.4% in C. sinensis, while in previous investigation it was 77.49% the peel oil of sweet orange followed by myrcene 6.27% [71,72]. Limonene (80.9%) and β-myrcene (4.19%) were the main constituents in fresh peel EO of C. sinensis [73].…”
Section: Discussioncontrasting
confidence: 44%
“…Other study showed that the C. sinensis peel EO had limonene, β-myrcene, decanal, β-pinene, and linalool, as major compounds with good antioxidant activity [70]. Limonene in the present study reached 73.4% in C. sinensis, while in previous investigation it was 77.49% the peel oil of sweet orange followed by myrcene 6.27% [71,72]. Limonene (80.9%) and β-myrcene (4.19%) were the main constituents in fresh peel EO of C. sinensis [73].…”
Section: Discussioncontrasting
confidence: 44%
“…In a previous reports ( Azar et al., 2011 ; Tao et al., 2009 ), limonene was observed as the main constituent (77.49 %) in the peel oil of sweet orange, followed by myrcene (6.27 %), α-farnesene (3.64 %) and γ-terpinene (3.34 %). The main compounds in C. sinensis from Uganda and Rwanda were limonene (87.9 and 92.5 %), myrcene (2.4 and 2.0 %), α-pinene (0.5 and 2.4 %) and linalool (1.2 and 0.9 %) ( Njoroge et al., 2009 ).…”
Section: Resultsmentioning
confidence: 63%
“…In previous reports [16,17], limonene was observed as the main constituent (77.49%) in the zest essential oil of sweet orange, followed by myrcene (6.27%), α-farnesene (3.64%), and γ-terpinene (3.34%). The main compounds in zest essential oil from Uganda and Rwanda were limonene (87.9 and 92.5%), myrcene (2.4 and 2.0%), α-pinene (0.5 and 2.4%), and linalool (1.2 and 0.9%) [18].…”
Section: Chemical Compositionmentioning
confidence: 72%